2023
DOI: 10.5534/wjmh.220099
|View full text |Cite
|
Sign up to set email alerts
|

Male Attitudes towards Infertility: Results from a Global Questionnaire

Abstract: In general, men are less likely to seek health care than women. Infertility is a global disease that afflicts approximately 15% of reproductive age couples and the male contributes to 40% of the diagnosable cause. Remarkably, no large or multi-national population data exist regarding men's perceptions about their infertility. The purpose of this study was to advance our knowledge about the infertile male's social experience regarding: (1) how they feel about their infertility, (2) what motivated them to seek h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…3 . These results have provided greater clarity about men’s diverse feelings about their infertility ( De Jonge et al , 2023 ). The study emphasizes the importance of men better identifying their emotions and more openly sharing their feelings, especially with their partner and with other men.…”
Section: Mrh: Society Economics Policy and Educationmentioning
confidence: 95%
See 1 more Smart Citation
“…3 . These results have provided greater clarity about men’s diverse feelings about their infertility ( De Jonge et al , 2023 ). The study emphasizes the importance of men better identifying their emotions and more openly sharing their feelings, especially with their partner and with other men.…”
Section: Mrh: Society Economics Policy and Educationmentioning
confidence: 95%
“…More positively, the EU has a number of EQA schemes in andrology and a well-established register of MAR units. However, there are regulatory differences among countries, and a recent survey revealed that substantial differences exist between European regions in social knowledge/awareness concerning MRH ( De Jonge et al , 2023 ).…”
Section: Mrh: a Global Perspectivementioning
confidence: 99%
“…In the context of a global decline in fertility rates, in which the male contribution still remains overlooked, it is critical to build strongly structured networks to guarantee the development of educational and scientific activities to forge new frontiers in the andrology field. Despite male factors contributing to 50% of infertility cases, major attention is paid to the examination of women 6,7 . Moreover, the exact causes of male infertility remain elusive in half of the cases due to its heterogeneous and complex etiology 8 .…”
Section: Figurementioning
confidence: 99%
“…Despite male factors contributing to 50% of infertility cases, major attention is paid to the examination of women. 6,7 Moreover, the exact causes of male infertility remain elusive in half of the cases due to its heterogeneous and complex etiology. 8 There is thus a strong need to promote basic, translational, and clinical research.…”
mentioning
confidence: 99%
“…Although male factors contribute to 50% of the infertility cases ( Agarwal et al, 2021 ; Levine et al, 2022 ; Salonia et al, 2021 ; Tiegs et al, 2018 ), studies of the underlying causes have been biased towards the examination of women. This may be influenced, in part, by social factors that have historically discouraged men from seeking routine health care unless in acute medical conditions ( de Jonge et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%